2011
DOI: 10.1108/00400911111147721
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and motivations of Polish students towards entrepreneurial activity

Abstract: PurposeThe Polish economy is continuing its expansion through the adoption of free market economics in the post‐communist era. To encourage this growth in a future where difficult global economic conditions are likely to persist, it is essential that entrepreneurial activity is encouraged within the next generation of graduates. This study aims to explore the attitudes and motivations of Polish students towards an entrepreneurship education programme.Design/methodology/approachTo achieve the research objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 42 publications
5
54
0
3
Order By: Relevance
“…Similarly, entrepreneurship education is considered as the most effective means of embedding an entrepreneurial culture in higher educational institutions (HEIs) by fostering students" entrepreneurial selfconfidence and developing the supply of future graduate entrepreneurs (Jones, Miller, Jones, Packham, Pickenell, &Zbierowski, 2011;Sesen, 2013). However, Ogundeji (2014) identified entrepreneurial self-efficacy as the major driving factor stimulating entrepreneurial career among graduates; hence need to be carefully considered in entrepreneurial training.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, entrepreneurship education is considered as the most effective means of embedding an entrepreneurial culture in higher educational institutions (HEIs) by fostering students" entrepreneurial selfconfidence and developing the supply of future graduate entrepreneurs (Jones, Miller, Jones, Packham, Pickenell, &Zbierowski, 2011;Sesen, 2013). However, Ogundeji (2014) identified entrepreneurial self-efficacy as the major driving factor stimulating entrepreneurial career among graduates; hence need to be carefully considered in entrepreneurial training.…”
Section: Introductionmentioning
confidence: 99%
“…Our focus on entrepreneurship education interventions in a university setting is governed by a fast-growing body of empirical research on entrepreneurship education outcomes that need to be studied [6]. We built our search and selection strategy on the established method of systematic literature review [18,23], which has been recognized within the entrepreneurship field in general (e.g., [24][25][26]) and within the field of entrepreneurship education in particular (e.g., [4,5]). Following Henry et al [11] we started by compiling a list of corresponding journals within which to do our literature search.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to methodological approaches, the absolute majority of the studies are quantitative ( = 12). There are only four notable exceptions with one qualitative article [25], and three others which employ a mixed method approach [28,31,32]. Among all the studies, questionnaire is the most common instrument for data collection, while researchers also used interviews as a data collection method [25].…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that entrepreneurship education programs contribute to the development of entrepreneurial intentions (Küttim et al, 2014). It is seen that many countries including England (Jones & Iredale, 2010), French (Klapper, 2004), German, Poland (Jones et al, 2011;Packham et al, 2010), Spain (Lanero et al, 2011), Italy (Dubbini & Iacobucci, 2004), Indonesia (Utami, 2017), Ghana (Dzisi & Odoom 2017) are trying to pursue entrepreneurship education especially at the level of bachelor's degree. Because, universities are considered as institutions playing a big role in obtaining both economic and social benefits thanks to their great capacity in both obtaining and disseminating knowledge (Vazquez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%